The association between blood vitamin E and blood pressure in an adult population with and without diabetes mellitus - Wan, Rong; Su, Yuhao; Zhu, Meilan; Huang, Ying (Frontiers in Endocrinology, 2024)
Previous studies on the association between vitamin E and blood pressure (BP) levels are controversial. Our study aimed to evaluate the association between blood vitamin E (alpha-tocopherol and gamma-tocopherol) levels and systolic and diastolic BP in an adult population with diabetes and without diabetes.Methods: Our study data were obtained from a biomarker project of the Midlife in the United States (MIDUS) study. A total of 1068 subjects were included, and the associations between alpha-tocopherol and gamma-tocopherol levels and systolic and diastolic BP were further analyzed by smooth curve and multivariate linear regression analyses.Results: Our smooth curve analysis showed an almost linear correlation between blood vitamin E (alpha-tocopherol and gamma-tocopherol) levels and systolic and diastolic BP. Furthermore, we found that blood gamma-tocopherol levels were positively and independently associated with systolic BP (B=0.427, 95% CI 0.067-0.787, P=0.020) and diastolic BP (B=0.289, 95% CI 0.072-0.507, P=0.009) when the data were adjusted for age, gender, body mass index (BMI), ever smoked cigarettes regularly, number of years of consuming alcohol and regular exercise or activity for 20 minutes or more at least 3 times/week. Consistently, blood alpha-tocopherol levels were also positively associated with systolic BP (B=0.150, 95% CI 0.064-0.235, P=0.001) and diastolic BP (B=0.056, 95% CI 0.004-0.107, P=0.035) after these variables were adjusted. However, these significant relationships exist only in subjects without diabetes, but not in subjects with diabetes.We observed for the first time that blood vitamin E (alpha-tocopherol and gamma-tocopherol) levels were positively associated with systolic and diastolic BP in subjects without diabetes.